The Effect of Financial Performance and Audit Quality on Company Value with Corporate Social Responsibility (CSR) Disclosure as a Moderating Variable - Ramadhani, Reni; Muhsin, Muhsin; Yunita, Khristina; Dosinta, Nina Febriana (STMIK Widya Cipta Dharma, 2025)
This study aims to determine the effect of financial performance and audit quality on company value with CSR disclosure as a moderating variable. This study is based on financial performance, with indicators such as Return on Assets (ROA), Audit quality with the indicator being the auditor's opinion, namely an Unqualified Opinion, CSR disclosure with indicators such as the Global Reporting Initiative (GRI) G4, and company value with indicators such as Tobin Q. The method used is quantitative with a focus on numerical data. The data used is secondary data obtained from the annual reports of companies classified in the plantation sector listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024. The analysis method used is panel data regression, which is a combination of time series data and cross-sectional data that provides efficiency in model estimation. In addition, a moderation test was conducted to determine the role of CSR in strengthening or weakening the relationship between financial performance and audit quality on company value. The results of the study indicate that financial performance has a negative and significant effect on company value, but audit quality and CSR disclosure as moderating variables do not have a significant effect on company value. Furthermore, financial performance with CSR disclosure as a moderator has a negative and significant effect on company value, while audit quality with CSR disclosure as a moderator does not have a significant effect on company value.